On the multiplicative Hv-rings derived from helix hyperoperations - Davvaz, Bijan; Vougiouklis, Sousana; Vougiouklis, Thomas (Utilitas Mathematica, 2011)
Algebraic hyperstructures are a generalization of the classical algebraic structures which, among others, are appropriate in two directions: (a) to represent a lot of application in an algebraic model, (b) to overcome restrictions ordinary structures usually have. Concerning the second direction the restrictions of the ordinary matrix algebra can be overcome by the helix-operations. More precisely, the helix addition and the helix-multiplication can be defined on every type of matrices. In this paper properties and examples on special classes of matrices are presented.